Optimization of malic anhydrate concentration in manufacturing PP-g-MA compatibilizer on test percent of grafting degree - DENNY AKBAR TANJUNG; NOVESAR JAMARUN; ROSLIANA LUBIS (Jurnal Natural)
The difference in polarity means that two or more materials cannot react, a connecting material such as a compatibilizer is needed to react between polar and non-polar materials. This research aims to determine the effect of maleic anhydride (MA) concentration on the process of grafting MA onto polypropylene (PP) chains with the help of benzoyl peroxide (BPO) as an initiator. The method used to mix these two materials uses the blending method using an internal mixer instrument and testing the percent degree of grafting using the titration method with three repetitions of the test.The research results showed that the highest percent grafting degree occurred at a concentration of 86% PP, 11% MA, and 3% BPO, with a value of 10.28%. The Spectroscopy Fourier Transform Infrared (FTIR) analysis of Polypropylene grafted maleic anhydride (PP-g-MA) showed the presence of new peaks at wavenumbers 1707cm-1 and 1162 cm-1.Increasing the concentration of maleic anhydride had no effect on increasing the percent degree of grafting.